Predictive factors of high societal costs among chronic low back pain patients - Mutubuki, Elizabeth N. (Eur J Pain, 2019)
BACKGROUND: Societal costs of low back pain (LBP) are high, yet few studies have been performed to identify the predictive factors of high societal costs among chronic LBP patients. This study aimed to determine which factors predict high societal costs in patients with chronic LBP. METHODS: Data of 6,316 chronic LBP patients were used. In the main analysis, high societal costs were defined as patients in the top 10% of cost outcomes. Sensitivity analyses were conducted using patients in the top 5% and top 20% of societal costs. Potential predictive factors included patient expectations, demographic factors (e.g. age, gender, nationality), socio‐economic factors (e.g. employment, education level) and health‐related factors (e.g. body mass index [BMI], general health, mental health). The final prediction models were obtained using backward selection. The model's prognostic accuracy (Hosmer–Lemeshow X (2), Nagelkerke's R (2)) and discriminative ability (area under the receiver operating curve [AUC]) were assessed, and the models were internally validated using bootstrapping. RESULTS: Poor physical health, high functional disability, low health‐related quality of life, high impact of pain experience, non‐Dutch nationality and decreasing pain were found to be predictive of high societal costs in all models, and were therefore considered robust. After internal validation, the models' fit was good, their explained variance was relatively low (≤14.1%) and their AUCs could be interpreted as moderate (≥0.71). CONCLUSION: Future studies should focus on understanding the mechanisms associated with the identified predictors for high societal costs in order to design effective cost reduction initiatives. SIGNIFICANCE: Identifying low back pain patients who are at risk (risk stratification) of becoming high‐cost users and making appropriate initiatives could help in reducing high costs.